Response to Robert H. Jackson. - Levine, Frances; LaBauve, Anna (Ethnohistory)
Responds to Robert H. Jackson's comments on the authors' article which focused on the sacramental records from Pecos Pueblo, New Mexico. Interpretations of the sacramental data; Need for a comparison of Pecos Pueblo data with other Pueblo and Hispanic communities in New Mexico; Suggestions made by Jackson regarding the article.